Comparison of Canine Overlap in Pediatric Patients Requiring Stainless Steel Crown Placement under General Anesthesia before and after the Procedure - Ghadimi, Sara (Front Dent, 2019)
OBJECTIVES: Despite the increasing popularity of pediatric dental treatments under general anesthesia, information is scarce regarding occlusal changes in patients receiving stainless steel crowns (SSCs) under general anesthesia. This study sought to compare canine overlap before and after general anesthesia in children receiving SSCs. In case of a change, the possibility of returning to the preoperative state and the time required for this process were also evaluated. MATERIALS AND METHODS: This interventional, before-and-after study was performed on 60 children between 2 to 7 years of age requiring dental treatment under general anesthesia. The contact point of the most prominent area of the maxillary primary canine and mandibular primary canine was marked before and immediately after general anesthesia and at one and two weeks postoperatively. The change in canine overlap was analyzed using repeated measures analysis of variance (ANOVA) and linear regression test. RESULTS: Canine overlap significantly decreased immediately after general anesthesia (P<0.05). The mean bite opening was 0.51±0.22 mm at the site of the right canine and 0.50±0.185 mm at the site of the left canine. These values returned to their normal preoperative state after one week (P<0.05). Repeated measures ANOVA showed significant differences in this respect between the time points (P=0.002). CONCLUSION: The occlusion and vertical dimension of pediatric patients may change following dental treatment under general anesthesia; the magnitude of change in canine overlap may vary depending on the class of occlusion and number of SSCs placed. These changes are temporary and often resolve within a week.